Transformasi Kecerdasan Buatan Terhadap Pengerjaan Tugas Kuliah Mahasiswa Management Semester 2 - Mintawati, Hesri; Pratiwi, Intan Deanida; Desianti, Lisa Chandrasari; Simangunsong, Bonse Aris Mandala Putra; Luckieta, Meiliani (JUDICIOUS, 2024)
This study aims to see if there is a change in the work of Nusa Putra students' coursework after a major update in the artificial intelligence (AI) sector. In a digital era that has changed greatly after AI, this research focuses on examining whether after AI there are changes in critical thinking, problem analysis, and also student literacy in coursework. The method used in the research is qualitative by means of interviews. The population we studied was NUSA PUTRA UNIVERSITY students majoring in Management Semester 2 and the sample used was 6 NUSA PUTRA UNIVERSITY students majoring in Management Semester 2. The results showed that artificial intelligence or AI is very influential on the mindset of critical thinking and also the level of literacy of a student, but the changes brought by AI can have both good and bad effects on students. It is also supported by the answers given by the respondents that AI or artificial intelligence can have both good and bad effects depending on who uses it and how it is used. This study emphasizes the importance of education in the use of AI to ensure that students' critical thinking, literacy and problem-solving skills are not diminished. The results also show that a balanced use of AI is the key to maximizing the advances in technology today. Keywords: Student Management, Critical Thinking, Literacy Level, Artificial Intelligence (AI)